Application of SPECT combined with CT and MRI in malignant tumors Clinical value in the diagnosis of bone metastasis - Li, Xiao; Shi, Wenda; Xu, Fan; Li, Qingshan; Xiao, Xu (Nepalese Journal of Cancer, 2022)
Objective：To evaluate the value of single-photon emission computerized tomography (SPECT) combined with CT and MRI in the diagnosis of bone metastasis of malignant tumors. Method：Eighty patients with bone metastasis from malignant tumors who admitted to Affiliated Hospital of Chengde Medical College were selected from March 2019 to June 2021. SPECT bone imaging, CT and MRI were used to analyze the regional distribution of primary tumor bone metastasis and the efficacy of three detection methods in the diagnosis of bone metastasis. Results: A total of 464 lesions were detected by SPECT and CT in the same scanning field，with SPECT detection rate of 92. 5% ( 429 /464) and CT detection rate of 77. 8% ( 361 /464) ( P＜0. 05). In addition，143 lesions were detected by SPECT beyond the same scanning field. A total of 321 lesions were detected by SPECT and MＲI in the same scanning field，with SPECT detection rate of 95. 6% ( 307 /321) and MRI detection rate of 82. 6% ( 265 /321) ( P＜0. 05)，and other 286 lesions were detected by SPECT beyond the same scanning field. In all，259 lesions were detected by CT and MＲI scans in the wild same scanning field. The detection rate was 71. 4% ( 185 /259) for CT，and 95. 7% ( 248 /259) for MRI( P＜0. 05). The sensitivity，specificity and accuracy of SPECT imaging combined with CT and MＲI were higher than single SPECT imaging，CT and MＲI ( P＜0. 05). Conclusion: SPECT may be the preferred screening modality for suspected bone metastases and when combined with CT and MＲI，it can clarify the regional distribution of bone metastasis from malignant tumors and improve the sensitivity，specificity and accuracy of diagnosis with high clinical significance.